Pengaruh Kepuasan Kerja dan Budaya Organisasi Terhadap Komitmen Kerja Guru SMP Negeri Sekecamatan Wonosobo Kabupaten Wonosobo - Utami, Kurnia Sari; Egar, Ngasbun; Juliejantiningsih, Yovitha (PGRI Kota Semarang, 2024)
Work commitment is an employee's willingness to continue to be part of the organization, as well as contribute to implementing the organization's vision and mission voluntarily and responsibly in completing the work that is the organization's goals. The aim of this research is to: determine the magnitude of the influence of job satisfaction and organizational culture together on work commitment. The research approach used is quantitative. This type of research uses associative research. The population of this study was 138 teachers and the research sample was 103 teachers. Data collection was carried out using a questionnaire. The research results show that: 1) The influence of job satisfaction on work commitment is 68.9%, 2) The influence of organizational culture on work commitment is 71.5%, 3) The influence of job satisfaction and organizational culture on work commitment is 75.9%. The conclusion of this research is that job satisfaction and organizational culture on work commitment are 0.759 or 75.9%. The author suggests that teachers carry out evaluations and develop learning, then teachers can also take part in training and seminars in order to increase competence which will lead to work commitment.